Land transport and road safety in Tungurahua - Mayorga Núñez, Fernando (2016)
This research shows the principle statistics for traffic accidents and the number of injured and dead people nationwide, in particular for the province of Tungurahua and its Cantons. It maked a comparative analysis between 2014 and 2015 that allowed the observation of the evolution of this data and its trends through the respective rates of variation, rates per thousand inhabitants and rates per hundred thousand inhabitants. This information gives a general idea of the current situation of ground transport and road security in Tungurahua. DOI: https://doi.org/10.31164/bcoyu.10.2016.614 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/614